Determining housing location using weighted product - Oktafianto; Sudrajat A.; Kawangit R.M.; Don A.G.; Huda M.; Saputri A.D.; Latif A.A.; Maseleno A. (Science Publishing Corporation Inc, 2023)
Housing is a set of houses that are established with different functions for the owner with equipped infrastructure that is equipped according to the owner wishes. In determining the location of housing in Pringsewu district, the criteria were needed in accordance with the consumer's wish. This study will be explained on how to determine the location of housing in Pringsewu district using weighted product method. Because the weighted product method can help decision making in determining the location of housing, the calculation only resulted the greatest value that will be chosen as the best alternative. 2018 Oktafianto et. al.